Causes and consequences of the late Holocene extinction of the marine flightless duck (Chendytes lawi) in the northeastern Pacific. (15th May 2021) - Jones, Terry L.; Coltrain, Joan Brenner; Jacobs, David K.; Porcasi, Judith; Brewer, Simon C.; Buckner, Janet C.; Perrine, John D.; Codding, Brian F.
Abstract: The extinction of California's flightless duck, Chendytes lawi, stands out in the faunal history of North America because it involved a marine animal that disappeared in the late Holocene, not in the terminal Pleistocene when humans arrived from Asia, nor with the more recent entry of Europeans and associated resource exploitation. Here we evaluate the duck's ecology by combining a stable isotopic evaluation of its feeding niche with records of human predation and climatic variation to evaluate (1) alternative influences on the duck's extinction and (2) possible ecological consequences of its disappearance. Results indicate that a mid-late Holocene increase in human population density coincided with a decrease in mean sea surface temperatures (SST) and an increase in SST variance, all of which were contemporaneous with the demise of the flightless duck ca. 2500 cal BP. Climate appears to be a main exogenous driver of this extinction event by not only negatively impacting flightless duck food availability, but positively impacting one of the duck's main predators: humans. Isotopic findings indicate the duck had a unique feeding ecology that overlapped equally with analog species reliant mostly on marine invertebrates (sea otters [ Enhydra lutris ]) and on fish (harbor seals [ Phoca vitulina ]). This dietary niche overlap suggests the duck's extinction could have opened foraging opportunities for harbor seals and sea otters. Otter numbers appear to have increased coincident with the duck's decline which also correlates with a decrease in size and abundance of red abalone ( Haliotis rufescens ), one of the otter's preferred prey. These correlations suggest that new feeding opportunities may have emerged for otters in the face of the duck's extinction, encouraging an increase in otter populations, which then had negative impacts on abalone that also were targeted by humans. Overall findings suggest the possibility of an unanticipated prehistoric precursor to the historic baseline of this nearshore ecosystem. Highlights: Pre-contact Holocene extinction of California's flightless duck was highly unusual. Duck's stable isotopic profile suggests feeding niche unlike any living duck. Isotope profile suggests feeding ecology akin to sea otters and harbor seals. Time series comparisons suggest extinction influenced by human predation and climate. Duck's disappearance may have affected changes in nearshore ecology.